Penerapan Teknik Relaksasi Genggam Jari Terhadap Nyeri Post Sectio Caesarea di Ruang Adas Manis RSUD Pandan Arang Boyolali - Mawarni, Dini Ika; Ika Silvitasari; Panggah Widodo (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Sectio caesarea is a surgical procedure to deliver a fetus by opening the abdominal wall and uterus. In Indonesia, the birth rate using the caesarean section method is quite high, reaching 17.6%. Childbirth with Sectio Caesaria will cause the mother to feel discomfort, one of which is pain originating from the abdominal incision. One of the treatments is using non-pharmacological techniques, namely the finger grip relaxation technique to reduce the level of pain in Post Sectio Caesarea patients. Providing finger-hold relaxation techniques can have a relaxing effect on the body and mind, naturally resulting in the release of endorphin hormones, these hormones are natural analgesics or painkillers from within the body which can reduce the intensity or scale of pain. To determine the results of applying the finger grip relaxation technique to reduce pain in post sectio Caesarea patients in the Adas Manis Room at Pandan Arang Hospital, Boyolali. This research is descriptive research using a case study approach. The subjects in this study were 2 respondents who were post sectio caesarea patients, the application was carried out for 3 days with a frequency of application once a day within 15 minutes. Based on the results of the application after being given the finger grip relaxation technique once a day for 3 days, there was a decrease in the pain scale from a moderate pain scale to a mild pain scale. The finger grip relaxation technique can be used as an effective non-pharmacological technique to reduce pain in Post Sectio Caesarea patients.